(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
The article describe the use of stylistic devices and cultural anylsis in the English translation of Abdullah Qodiri’s novel “Days Gone by”. The article investigates the stylistic transformations in the English translations of A.Qodiri’s novel “Days Gone By”. The main focus is given to the translations of metaphor.